Building Flats Through Waqf Land: Legal Breakthrough And Obstacles - Muhammad Maksum (AHKAM : Jurnal Ilmu Syariah, 2017)
Legal Breakthrough and Obstacles. The ratification of Law No.20/2011 regarding flats has led us to a legal breakthrough particularly on the merger opportunity between waqf and flats. Such opportunity offers legal distinctive solution such as owning the flats based on the Right to Ownership of Buildings Title (Sertifikat Kepemilikan Bangunan Gedung/SKBG) and the imposition of collateral in fiduciary. On the other hand, this law also brings out legal issues related to the rights and responsibilities of the parties in the lease contract or the cooperation between the waqf supervisor and the manager of the buildings and the tug-of-war concerning the dispute settlement authority between general and syariah courts. DOI: 10.15408/ajis.v17i1.6229